Assessing the possibility of charging for public leasehold renewal in China. (November 2019) - Tong, De; Wang, Zhenguo; Hong, Yu Hung; Liu, Chengming
Highlights: Difficulty of charging the renewal of public land leases is not just about politics. First attempt to use a comprehensive framework to examine lease renewal conflicts. Ascertain quantitatively if lessees in Shenzhen pay less for public leasehold land. Identify institutional barriers to the collection of lease renewal fees in Shenzhen. Abstract: In countries where public land leasing systems exist, government lessors have faced strong resistance on the part of lessees to charging fees to renew extended-term land leases. Many scholars have argued that this outcome is largely due to politics, i.e., not wanting to alienate constituents. In this paper, we look deeper into this issue guided by an analytical framework, which includes lessees' perceptions of land property rights, the amount they pay for public leaseholds, and institutional issues related to the implementation and enforcement of lease renewal policies. By applying the framework to Shenzhen, China, we found that lessees recognize that their leasehold rights have a time limit and that they have paid a lower price for leasing land. This awareness on the part of the lessees notwithstanding, the absence of the institutions necessary to facilitate negotiation and conflict resolution could impede the ability of the government to successfully levy lease renewal fees in Shenzhen. The application of the framework shows its utility in helping governments in China and elsewhere to examine lease renewal problems in detail and design relevant solutions to fit varying contexts.